Co-Optimization of Generation and AC Transmission Networks, Considering Reactive Power Allocation and Network Power Losses - Chillogalli, Jose E. [UNESP]; Torres, Santiago P.; Romero, Ruben A. [UNESP]; Chumbi, Wilson E. [UNESP]; Astudillo-Salinas, Fabian; Ochoa-Correa, Danny (Institute of Electrical and Electronics Engineers (IEEE), 2024)
Generation and transmission network expansion planning (GTNEP) co-optimization models have been developed to enable simultaneous decisions considering investment and operational components. Most works solve the GTNEP using linearized models without considering voltage variables, reactive power constraints, and network power losses, thus resulting in a loss of model fidelity and leading to either sub-optimal or non-feasible expansion plans. Therefore, this work addresses the GTNEP problem by integrating the planning of new generation power plants, transmission lines, reactive power allocation, and the evaluation of network power losses, using the AC model to assess the operational problem. Therefore, the integrated AC-GTNEP problem is tackled using meta-heuristic optimization techniques. The approach was implemented using the Julia programming language and evaluated using the 6-bus Garver, the IEEE 24-bus, and the IEEE 118-bus test systems. The results illustrate that the proposed integrated GTNEP approach yields more cost-effective expansion plans compared to the sequential approach, with total savings of approximately 11.30%, 8.8%, and 2.5% when applied to each test system, respectively.
Keywords: AC model; co-optimization; generation expansion planning; integrated planning; transmission network expansion planning